Detection and diagnosis of large airway collapse: a systematic review - Alexandros Mitropoulos (ERJ Open Research, 2021)
Large airway collapse (LAC) is a frequently encountered clinical problem, caused by tracheobronchomalacia +/− excessive dynamic airway collapse, yet there are currently no universally accepted diagnostic criteria. We systematically reviewed studies reporting a diagnostic approach to LAC in healthy adults and patients, to compare diagnostic modalities and criteria used. Electronic databases were searched for relevant studies between 1989 and 2019. Studies that reported a diagnostic approach using computed tomography (CT), magnetic resonance imaging or flexible fibreoptic bronchoscopy were included. Random effects meta-analyses were performed to estimate the prevalence of LAC in healthy subjects and in patients with chronic obstructive airway diseases. We included 41 studies, describing 10 071 subjects (47% female) with a mean±sd age of 59±9 years. Most studies (n=35) reported CT findings, and only three studies reported bronchoscopic findings. The most reported diagnostic criterion was a ≥50% reduction in tracheal or main bronchi calibre at end-expiration on dynamic expiratory CT. Meta-analyses of relevant studies found that 17% (95% CI: 0–61%) of healthy subjects and 27% (95% CI: 11–46%) of patients with chronic airways disease were classified as having LAC, using this threshold. The most reported approach to diagnose LAC utilises CT diagnostics, and at a threshold used by most clinicians (i.e., ≥50%) may classify a considerable proportion of healthy individuals as being abnormal and having LAC in a quarter of patients with chronic airways disease. Future work should focus on establishing more precise diagnostic criteria for LAC, relating this to relevant physiological and disease sequelae.